Persistence and protection of the Vulnerable Bengal slow loris Nycticebus bengalensis in Assam and Arunachal Pradesh, north-east India. Issue 1 (January 2015) - Das, Nabajit; Nekaris, K.A.I.; Biswas, J.; Das, J.; Bhattacharjee, P.C.
Abstract The Bengal slow loris Nycticebus bengalensis is the only strepsirrhine primate in north-east India. It is categorized as Vulnerable on the IUCN Red List. The limited information on its status and ecology is the main hindrance to developing a conservation strategy for this species in India. Therefore during February 2009–May 2010 we surveyed the species in 16 protected areas in Assam and one protected area in Arunachal Pradesh. We used recce transects to estimate encounter rates for the species. A team of 3–4 conducted night-time surveys (18.00–03.00) on foot, covering 370 km over 99 full and 28 partial nights. We recorded lorises a total of 22 times in nine protected areas in Assam and three times in the protected area in Arunachal Pradesh. The mean distance of lorises from transects at the time of encounter was 15.04 m, at a mean height of 12.36 m above ground. The encounter rate was 0.06–0.2 lorises per km, which is relatively low compared to encounter rates for slow lorises elsewhere in their range but higher than recorded by other studies in north-east India. We found that despite hunting and habitat loss Bengal slow lorises still exist in Assam and Arunachal Pradesh, albeit patchily within a forest block. The protected area network in these states is important for their conservation.